PENGARUH JANGKA WAKTU PINJAMAN DAN STATUS PEKERJAAN TERHADAP TINGKAT KELANCARAN PENGEMBALIAN KREDIT - Sari, Meita Sekar; Akbar, Aidin (LPPM UNIVERSITAS BINA INSAN, 2019)
Pegadaian Syariah is a State-Owned Enterprise (BUMN) that runs a pawnshop system in accordance with Islamic law. Financing / credit is the provision of money or equivalent bills, based on an agreement between a financial institution and another party that requires the financed party to return the money or bill after a certain period of time with compensation or profit sharing. Islamic pawnshops can provide financing / credit to customers. This study aims to analyze the Effect of Large Loans, Loan Duration, Job Status on the Level of Smooth Credit Returns at PT Pegadaian Syariah UPS Urip Sumoharjo. The data used in the study were secondary data with a population of 487 customers, and a sample of this study which included 56 customers at PT Pegadaian Syariah UPS Urip Sumoharjo. The analytical tools used are chi square and logistic regression. The results showed the smoothness of repayment of credit loans affected Loan Term, and job status. The results of the analysis of the two variables, namely Loan Period, and Employment Status have an influence on the rate of return on credit at PT Pegadaiain Syariah UPS Urip Sumoharjo. Sharia Pegadaiain parties are expected to pay attention to these variables in the analysis of lending.